Anti-thrombotic agents derived from snake venom proteins. Issue 1 (October 2016) - Huang, Tur-Fu; Hsu, Chun-Chieh; Kuo, Yu-Ju
Abstract Snake venoms affect blood coagulation and platelet function in a complex manner. However, two classes of venom proteins, snaclecs and disintegrins have been shown to specifically target receptors including GPIb, α2β1, GPVI, CLEC-2 and integrins αIIbβ3, αvβ3, α5β1 expressed on platelets, endothelial cells, phagocytes, tumor cells, thus affecting cell-matrices and cell-cell interactions. Here, we focus on disintegrins, a class of low molecular mass Arg-Gly-Asp(RGD)/Lys-Gly-Asp(KGD)-containing, cysteine-rich polypeptide derived from various viper snake venoms. This review describes the potential applications of disintegrins in field of integrin-related diseases, especially arterial thrombosis, angiogenesis, tumor progression and septic inflammation. In addition, a novel RGD-containing disintegrin TMV-7 is being developed as a safer antithrombotic agent with minimal side effects, such as thrombocytopenia and bleeding.